Factors affecting access to subcutaneous medicines for people dying in the community. (2nd September 2020) - Tait, Paul; Sheehy, Kylee; Sindhusake, Doungkamol; Muscillo, Nina
Abstract : Objectives: Common terminal phase symptoms include pain, dyspnoea, anxiety, terminal restlessness, nausea and noisy breathing. This study identified the proportion of community pharmacies across two Australian states stocking medicines useful in managing terminal phase symptoms, while exploring factors considered predictive of pharmacies carrying these medicines. Methods: Community pharmacies from across the states of New South Wales (NSW) and South Australia (SA) were concurrently mailed a survey. Respondents were asked questions relating to medicines stocked, expiry date of stock, awareness of people with palliative care needs and demographic characteristics of the pharmacy. A 'prepared pharmacy' was defined as a pharmacy that held medicines useful in the management of terminal phase symptoms. Results: The proportion of prepared pharmacies across NSW and SA was 21.9%. Multiple logistic regression demonstrated eight predictors of prepared pharmacies, of which awareness of people with palliative needs using their service was the strongest. Conclusions: One-fifth of community pharmacies carry formulations useful in managing terminal phase symptoms. The main factor associated with this was awareness of people with palliative needs using the pharmacy. Strategies that engage with pharmacists in anticipation of the terminal phase are critical, supporting people with palliative needs to remain at home to die, if desired.